أدب العودة ومضامينه في الشعر الفلسطيني = Literary works on the theme of return and its contents in Palestinian poems = Tema kepulangan dan kandungannya dalam sastera Palestin - Hussein, Nasr El Din Ibrahim Ahmed; Mohkles Yahya Barzak, Maryam (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
لأدب مرآة الواقع حوله على اختلاف أجناسه، وكلُّ تطوُّرٍ يطرأ على الواقع ينعكس –بلا شكٍّ- على الأدب ويتجلَّى فيه، وقد كان الشعراء والأدباء أوَّلَ من تأثَّر بالواقع فسجَّلوا ذلك في أدبهم فظهر شعراً ونثراً، ولأنَّ القضية الفلسطينيَّة شكَّلت أهميَّة ًمركزيَّةً في أحداثها على الشَّأن العربي والإسلامي وخاصة بعد نكبة عام ثمانية وأربعين؛ فإنَّ الدَّور الأبرز ظهر جليَّاً عند طبقة المثقَّفين. لقد نشأ ما اصْطُلِحَ على تسميته (أدبُ العودة) والذي جاء ردَّة فعلٍ ونتيجة للنكبة وما تبعها من تهجير الآلاف إلى الشَّتات والمنفى، هذا الأدب بخصوصيته تميَّز بسماتٍ خاصَّة إبداعيَّة ومضامين متنوِّعَةً احتواها، ألقتْ الضَّوء على مُجريات القضيَّة وأكَّدت في مُجملها على حقِّ العودة للأرض، ورفضتْ أيَّ حلولٍ سياسيَّة للتوطين ونسيان الحقوق. يُسلِّط هذا البحث الضَّوء على أبرز المضامين لأدب العودة من أربعة محاور أساسيَّة هي: حقُّ العودة، وملامح وتفاصيل الوطن، والشَّوق والحنين للوطن، والبذل والتَّضحية من المقاومة والشَّهادة والاعتقال، ومُرَكِّزاً على الجانب الشِّعري دون النَّثري للشعراء الفلسطينيين بعد النكبة. وقد خلص البحث إلى تنوُّع المحاور التي تناولها أدب العودة تنوُّعَ الحياة وظروفها المُشَكِّلة لتجربة الشعراء، فكتبوا تحت عناوين مختلفة سارتْ جنباً إلى جنب في أهميَّتها مع القضيَّة السياسيَّة والمسلَّحة الثائرة. *************************************************************************************** Literature, regardless of it various genres, is a mirror to the reality it represents. Any change in reality is reflected without doubt in it. Poets and writers are the first to be affected by a change in reality and subsequently making its reflection in their works. As the Palestinian cause has its own central significance on the Islamic and Arabic situations especially after the 1948 Nakbah, this reflection had stood out the most among the learned stratum of the society. A term called the literature of return had sprung up in reaction to he Nakbah that resulted in the migration of thousands to scattered nations. This type of literature has its own stylistic characteristics and contents that shed lights on the issue and emphasize on their rights of return which rejected any proposal to resettlement and the ignoring of rights. The study would shed light on four major themes: the right to return, the features and characteristic of their birth place, the longing to their homes, sacrifice, struggle, martyrdom and detention. The study will focus on the poems of the Palestinian poets in this regard after the Nakbah. The study concluded that this type of literature consists of various themes that shape up the different perspectives of the poets. They wrote under various topics that are hand in hand with the political and revolutionary reality of the issue of Palestine. **************************************************************************************